Clinical Risk Factors of Post-Surgery Hemorrhage in Patients Undergoing Tonsillectomy: Post-Surgery Hemorrhage in Patients Undergoing Tonsillectomy - Bhatti, Sanaullah; Tarar, Javed Mirdad; Ashraf, Muhammad Asif; Tahir, Mahreen (Pakistan Journal of Health Sciences, 2025)
Post-tonsillectomy hemorrhage is rare but life-threatening and poses a critical emergency. However, limited research has been conducted on adults undergoing tonsillectomy. Objective: To analyze the predictors of post-tonsillectomy hemorrhage in adults undergoing tonsillectomy. Methods: A retrospective study was conducted in the ENT and Surgery Department of Bakhtawar Amin Hospital from April 2024 to Jan 2025. A total of 150 adult patients underwent bilateral tonsillectomies for recurrent tonsillitis, obstructive sleep apnea, tonsillar hypertrophy, palmoplantar pustulosis, or IgA nephropathy. The surgery was performed according to the usual procedure under anesthesia. Age, gender, duration of surgery, obesity, antibiotic administration, smoking status, and type of analgesia were recorded as probable predictors of hemorrhage. Smoking status included current smokers, non-smokers, and former smokers who had stopped smoking at least 1 month before the procedure. Results: There was a significant difference between smokers and non-smokers (OR=3.52, 95% CI: 1.76- 6.68, p<0.001) and smokers and former smokers (OR=3.55, 95% CI: 1.63-7.61, p<0.003). Male gender (OR: 4.03, 95% CI: 1.63-9.89, p=0.005) and NSAID (OR: 7.87, 95% CI: 1.007-63.53, p=0.0502) were significantly associated with post-operative hemorrhage. Smoking status (p=0.052) and older age (p=0.005) were significant risk factors in the primary hemorrhage group, and smoking status (p<0.001) and male gender (p=0.010) were significant in the secondary hemorrhage group. Conclusions: Post-tonsillectomy hemorrhage had a significant association with male gender, smoking status, and administration of NSAIDs during surgery. Therefore, it is advisable for surgeons to strongly suggest that patients maintain a healthy lifestyle before surgery and opt for other analgesics to prevent the risk of hemorrhage.